Outcomes of carotid sparing intensity‐modulated radiotherapy for early stage glottic cancer in 201 patients: Multicenter study of Turkish Radiation Oncology Society/TROD‐01‐007. Issue 8 (21st May 2022) - Bicakci, Beyhan Ceylaner; Mustafayev, Teuta Zoto; Cetinayak, Oguz; Igdem, Sefik; Birgi, Sumerya Duru; Meydan, Deniz; Demircioglu, Fatih; Atalar, Banu; Ozyar, Enis; Akman, Fadime
Abstract: Background: To assess and report clinical outcomes after carotid sparing intensity‐modulated radiotherapy for early stage laryngeal cancer. Methods: We retrospectively analyzed 201 patients with early stage glottic laryngeal cancer treated with carotid sparing intensity‐modulated radiotherapy (IMRT)/volumetric modulated arc therapy (VMAT) techniques in six TROD centers. Results: After a median follow‐up of 31 months the actuarial 1‐ and 3‐year local and locoregional control rates were 99.4% and 94.7%, 98.4% and 93%, respectively. T classification, anterior commissure involvement, IMRT technique, and type of fractionation were not found to be prognostic for local control. Overall, eight patients had lost their organ function due to recurrence or toxicity. Grade 3 and 4 acute laryngeal edema was seen in eight (4%) and one (0.5%) of patients, respectively. Grade 3 and 4 late laryngeal edema developed in two (1%) and one patient (0.5%), respectively. Conclusion: Oncologic outcomes of patients treated with carotid sparing IMRT were excellent; comparable with historical series, with acceptable side effects. Longer follow‐up is needed to estimate long term effect on stroke.